Nilai-Nilai Pendidikan Keluarga Islam dalam Narasi Mimpi Nabi Yusuf pada QS. 12:1–6 - Musfirah; Halimah Basri; Ahmad Mujahid (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2026)
Contemporary Muslim families increasingly encounter challenges related to character formation, parent–child communication, and the transmission of religious values. While the narrative of Prophet Yusuf has been widely examined from theological, literary, and psychological perspectives, limited attention has been given to its contribution as a framework for Islamic family education, particularly in the opening narrative of Qur'an 12:1–6. This study aims to explore the Islamic family educational values embedded in the narrative of Prophet Yusuf's dream and to examine their relevance for contemporary family education. This qualitative library research employs a tahlili approach to Qur'anic interpretation by analyzing Qur'an 12:1–6 through classical and contemporary tafsir literature, supported by relevant scholarly works on Islamic education and family studies. The findings reveal that the narrative embodies five interconnected educational values: strengthening faith, cultivating respect toward parents, fostering affection within the family, nurturing optimism, and promoting constructive parent–child communication. These values are reflected in the compassionate interaction between Prophet Ya'qub and Prophet Yusuf, demonstrating an educational model grounded in spirituality, wisdom, emotional support, and parental guidance. The study concludes that the narrative of Prophet Yusuf's dream offers a holistic framework for Islamic family education that remains relevant for nurturing moral character, spiritual development, and harmonious family relationships in contemporary Muslim society.